2021
DOI: 10.1002/ehf2.13352
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diastolic dysfunction on outcome in heart failure patients with mid‐range or reduced ejection fraction

Abstract: AimsThe role of diastolic dysfunction (DD) in prognostic evaluation in heart failure (HF) patients with impaired systolic function remains unclear. We investigated the impact of echocardiography-defined DD on survival in HF patients with mid-range (HFmrEF, EF 41-49%) and reduced ejection fraction (HFrEF, EF < 40%). Methods and results A total of 2018 consecutive hospitalized HF patients were retrospectively included and divided in two groups based on baseline EF: HFmrEF group (n = 951, aged 69 ± 13 years, 74.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Our results showed that among HFmrEF patients with or without increased blood biomarkers (from 0 to 4), CV events rate increased from 10.4% to 31.1% at 3 months after discharge, from 14.4% to 45.1% at 12 months after discharge, and from 47.0% to 64.6% at 33 months after discharge. Determination of these 4 circulating biomarkers, together with increased E/e′ (>18) and PASP (>35 mmHg), two echocardiographic indices indicating the presence of diastolic dysfunction, 22 might thus be a reliable strategy of risk stratification of HFmrEF patients to filter out the high‐risk HFmrEF patients. It is reasonable to administrate a more intensive HF medication plan and closer follow‐up for patients with high‐risk HFmrEF, which defined by above 4 serum biomarkers in combination with or without the two echocardiographic indices (E/e′ > 18 and PASP >35 mmHg).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that among HFmrEF patients with or without increased blood biomarkers (from 0 to 4), CV events rate increased from 10.4% to 31.1% at 3 months after discharge, from 14.4% to 45.1% at 12 months after discharge, and from 47.0% to 64.6% at 33 months after discharge. Determination of these 4 circulating biomarkers, together with increased E/e′ (>18) and PASP (>35 mmHg), two echocardiographic indices indicating the presence of diastolic dysfunction, 22 might thus be a reliable strategy of risk stratification of HFmrEF patients to filter out the high‐risk HFmrEF patients. It is reasonable to administrate a more intensive HF medication plan and closer follow‐up for patients with high‐risk HFmrEF, which defined by above 4 serum biomarkers in combination with or without the two echocardiographic indices (E/e′ > 18 and PASP >35 mmHg).…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic implications of E/e' have been investigated mainly in non-surgical patients with various heart diseases. A retrospective review of 2018 hospitalized patients with heart failure, the all-cause mortality over more than 6 years increased in proportion to the severity of diastolic dysfunction, and in patients with EF < 40%, severe diastolic dysfunction was independently associated with increased all-cause mortality [23]. In a study enrolling 230 patients with non-valvular AF, the cumulative survival during follow-up (average 245 days) was signi cantly lower in subjects with E/e' > 15 than in those with E/e' ≤ 15, and the high E/e' was an independent predictor of mortality [24].…”
Section: Discussionmentioning
confidence: 99%
“…This finding might be interpreted as a hint for DD being the ‘straw that breaks the camel’s back’ for CV death in HFrEF, but not in HFmrEF patients. MEE might be a part of mechanism ( Liu et al, 2021 ). As a simple, feasible and noninvasive way to evaluate MEE, we showed that echocardiogram-derived MEE correlates well the severity of diastolic dysfunction in patients with HFpEF.…”
Section: Discussionmentioning
confidence: 99%